Optimalisasi Zakat Produktif Berbasis Maqashid Syariah untuk Pemberdayaan Ekonomi Masyarakat Kraksaan, Probolinggo - Ainul Yakin; Ahmad Nuril Madani; Najmus Shobah Almutanaffas; Moh. Yatim; Hasan Widad Fahmi Firdaus; Muhammad Hidayat (Yayasan Literasi Altruis Khatulistiwa, 2025)
Zakat is a strategic instrument in Islam that carries both devotional and socio-economic dimensions. However, in many regions, including Keboangung Village, Kraksaan District, Probolinggo Regency, zakat management still tends to be consumptive and lacks a long-term empowerment orientation. The distribution of zakat as mere direct aid fails to sustainably transform the condition of the mustahiq (zakat recipients). This program aims to optimize zakat management through a productive approach based on maqashid sharia as both a philosophical foundation and an operational framework for empowering the local economy. The maqashid sharia approach encompasses the protection of religion (din), life (nafs), intellect (‘aql), lineage (nasl), and wealth (mal). The implementation methods include socialization and education on the values of maqashid sharia for zakat managers and the local community, skill development and business management training for mustahiq, as well as intensive mentoring in the establishment and growth of business units funded by zakat. The results of this community service activity show positive outcomes in optimizing productive zakat based on maqashid sharia for economic empowerment. Through education and socialization efforts targeting key stakeholders, there has been an increase in understanding regarding the importance of transforming zakat management from a consumptive to a productive approach grounded in the five core objectives of maqashid sharia: the protection of religion, life, intellect, lineage, and wealth